2018
DOI: 10.1111/peps.12285
|View full text |Cite
|
Sign up to set email alerts
|

“I (might be) just that good”: Honest and deceptive impression management in employment interviews

Abstract: Applicant use of impression management (IM) tactics plays a central role in employment interviews. IM includes behaviors intended to create an impression of competence and likability, and avoid negative impressions. Applicants can influence interviewers’ impressions using both honest and deceptive IM, but measurement of IM has yet to distinguish these two constructs. The goal of the present research was to develop a self‐report Honest Interview Impression Management (HIIM) measure and use this to investigate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
246
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(274 citation statements)
references
References 74 publications
(261 reference statements)
25
246
1
2
Order By: Relevance
“…Warmth, however, seems difficult to convey through verbal ingratiation, and may be more effectively conveyed through nonverbal tactics such as smiling, nodding, and leaning forward (Cuddy et al, 2011). Moreover, because the current study used a purely honest measure of self-reported IM (Bourdage et al, 2018), the results indicate that interviewees can be very successful in interviews by honestly selling themselves (i.e., honestly self-promoting) without resorting to lying or stretching the truth. In summary, to increase chances of interview success, interviewees should engage in honest self-promotion to appear more competent, as well as attempt to appear interpersonally warm.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Warmth, however, seems difficult to convey through verbal ingratiation, and may be more effectively conveyed through nonverbal tactics such as smiling, nodding, and leaning forward (Cuddy et al, 2011). Moreover, because the current study used a purely honest measure of self-reported IM (Bourdage et al, 2018), the results indicate that interviewees can be very successful in interviews by honestly selling themselves (i.e., honestly self-promoting) without resorting to lying or stretching the truth. In summary, to increase chances of interview success, interviewees should engage in honest self-promotion to appear more competent, as well as attempt to appear interpersonally warm.…”
Section: Discussionmentioning
confidence: 76%
“…A final and very important strength of this study is that it used separate measures of self‐reported honest and deceptive IM (Bourdage et al, ). Many past measures of IM have not distinguished between honest and deceptive IM and have combined the two types of IM within the same measures (Bourdage et al, ). The current study used the only existing scale that exclusively measures honest IM to assess honest IM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applicants may engage in different types of deceptive IM, including misleading interviewers by exaggerating or outright lying about their qualifications, hiding or lying about negative aspects of their employment history, pretending to be a good fit with the organization, or insincerely flattering the interviewer or organization (Levashina & Campion, ). Studies have shown that many applicants fake in interviews, with two of the largest studies showing 17%–69% of applicants engage in certain forms of faking (Bourdage, Roulin, & Tarraf, ) and that over 90% of undergraduate job candidates engage in faking to some extent (Levashina & Campion, ). Compounding this problem, research indicates that interviewers are poor at detecting when an applicant is faking (Roulin, Bangerter, & Levashina, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Given these findings, there has been great interest in understanding the antecedents of interview faking (Levashina & Campion, ), including who is most likely to fake in interviews (e.g., applicant characteristics), and the situational factors that impact applicant faking in the interview (e.g., question type). A burgeoning body of evidence has demonstrated that the most replicated predictors of interview faking (across both individual and multiple interviews) are applicant personality traits, such that individuals low in traits such as Honesty–Humility and Conscientiousness are most likely to engage in faking (Bourdage et al, ; Buehl & Melchers, ; Law, Bourdage, & O’Neill, ; Roulin & Bourdage, ). Although these studies give us insight into who is most likely to fake in the interview, they have provided little insight into the reasons why particular traits are associated with interview faking.…”
Section: Introductionmentioning
confidence: 99%